Analisis dan Perancangan Sistem Informasi Eksekutif Pemasaran pada Distributor Alat Tulis Kantor: Studi Kasus pada Benza Prima - Mohammad Subekti; Raden Bagus Rhesa Dharma Widjaya; Eileen Heriyanni; Giovani Dewi (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Executive information system (EIS) has been widely used in enterprises and institutions to help the executives make decisions quickly and accurately for the organization's business needs. A research is conducted to create a marketing executive information system that can produce analytic reports and comparison reports for the executive of Benza Prima. For information search the fact finding techniques is utilized by conducting surveys directly to the company to study the company needs and the running procedures. The executive information system design uses Object Oriented Analysis and Design (OOAD) methodology. The research results in an executive information system that produces report in forms of pivot tables and charts to help the Benza Prima executives make decisions. The marketing executive information system design is expected to provide analytic information that can be used by the Benza Prima executive as an analytic tool in planning marketing strategies.